Intimate Partner Violence May Be One Mechanism by Which Male Partner Socioeconomic Status and Substance Use Affect Female Partner Health - Assari, Shervin; Jeremiah, Rohan D. (Frontiers in Psychiatry, 2018)
Background: Although male partner’s poor socio-economic (SES) and mental health increase the risk of male to female intimate partner violence (IPV), it is not known if IPV is a mechanism by which male partner’s SES and mental health is associated with perceived health among female partners. Objectives: To test the association between male partners’ SES and mental health on male to female IPV, and female partners’ trajectory of perceived health. Materials and Methods: For this longitudinal study we used data from the Fragile Families and Child Wellbeing Study (FFCWS), an ongoing population-based cohort. Male and female partners’ SES, anxiety, depression, and substance use, and their relationship status were measured at baseline. IPV victimization was also asked among female partners’ at baseline. Female partner’s subjective health was measured 3 times (baseline, 2 years later, and 4 years later). Using AMOS, we fitted two structural equation models (SEM) for data analysis. In Model I we tested direct paths from male partner’s SES and mental health to female partner’s perceived health, in the absence of IPV. In the Model II we conceptualized female partner’s IPV victimization between male partner’s SES and mental health and female partner’s perceived health. In both models we controlled for the effect of female partners’ SES and mental health. Results: In Model I, male partner’s SES and substance use but not anxiety and depression were associated with trajectory of perceived health of female partner. In Model II, male partner’s SES, substance use, anxiety, and depression were associated with IPV, which was in turn associated with partner’s perceived health. Conclusions. IPV is one of the mechanisms by which male partner’s mental health influences female partner’s wellbeing. IPV may be a vehicle by which male partner’s poor SES and depression reduce wellbeing of female partners. Prevention of IPV may reduce the effect of male partners’ anxiety and depression on female partner subjective health. Prevention of IPV may not prevent the effect of male partners’ SES and substance use on female partner’s wellbeing.